A method of calculating urban-scale solar potential by evaluating and quantifying the relationship between urban block typology and occlusion coefficient: A case study of Wuhan in Central China - Xu, Shen; Li, Zhixin; Zhang, Chen; Huang, Zhaojian; Tian, Jia; Luo, Yongqiang; Du, Hu (Sustainable cities and society, 2021)
•An urban block classification method based on clustering algorithm is applied.•Occlusion coefficient shows three main groups, which represent three types of urban block.•Occlusion factors of urban block types helps to revise the evaluation of urban roof solar energy potential.•A method for quickly obtaining solar energy potential based on 2D urban roof images is introduced.•Correlation between coefficient and latitude of cities has been discussed, which shows high relevance and can help to assess other cities. Relevant research shows that the potential of solar energy utilization varies greatly in different occlusion conditions. However, existing methods of assessing macro-city-scale solar roof utilization potential are not capable of considering the factor of mutual occlusion between urban buildings. To measure the overall solar photovoltaic utilization potential of the city, it is necessary to quantify the occlusion caused by the urban environmental building roof. This paper uses typical high-density blocks to quantify differences of occlusions on the building roof caused by urban blocks and building functions. Taking Wuhan as an example, a large number of urban blocks which form indicators were counted were selected as research samples, the data sets covers six types of morphological indicators to classify the urban blocks, and then the above blocks was modelled to simulate the solar radiation in order to obtain the values and combine with their morphological parameters, which will help to get roof solar occlusion factors by linear regression ways. The overall roof occlusion coefficient result of Wuhan is 0.079. By applying the above-mentioned occlusion coefficient to measure the solar energy potential of Hongshan District in Wuhan, the annual photovoltaic power generation was calculated to be able to reach 168.02GWh.